2016
DOI: 10.1038/srep39125
|View full text |Cite
|
Sign up to set email alerts
|

Nanofocusing of the free-space optical energy with plasmonic Tamm states

Abstract: To achieve extreme electromagnetic enhancement, we propose a plasmonic Tamm states (PTSs) configuration based on the metal-insulator-metal Bragg reflector, which is realized by periodically modulating the width of the insulator. Both the thick (2D) and thin (3D) structures are discussed. Through optimization performed by the impedance-based transfer matrix method and the finite difference time domain method, we find that both the electric field and magnetic field intensities can be increased by three orders of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The finite depth of the system and the surrounding media introduce a significant effect on loss in the system. Nevertheless, it was shown that above a certain height ( h = 50 nm), 2D and 3D models provide almost similar results in particular as concerns the positions of the resonant modes in the transmission spectra (Niu et al 2016); however, their shapes and widths are considerably affected. The analytical results of section 2.2 will be compared with numerical simulations based on a two-dimensional (2D) finite element method used to simulate the transmission spectra through the plasmonic device depicted in Fig.…”
Section: Analytical and Numerical Results In The Infrared Domainmentioning
confidence: 99%
“…The finite depth of the system and the surrounding media introduce a significant effect on loss in the system. Nevertheless, it was shown that above a certain height ( h = 50 nm), 2D and 3D models provide almost similar results in particular as concerns the positions of the resonant modes in the transmission spectra (Niu et al 2016); however, their shapes and widths are considerably affected. The analytical results of section 2.2 will be compared with numerical simulations based on a two-dimensional (2D) finite element method used to simulate the transmission spectra through the plasmonic device depicted in Fig.…”
Section: Analytical and Numerical Results In The Infrared Domainmentioning
confidence: 99%
“…This design is the most used geometry in MIM waveguide simulations as it is less time consuming than the fully realistic 3D MIM waveguides (Figure 1b), which have a finite height h in the z-direction and are deposited on a SiO 2 substrate. However, it was shown that, beyond a specific h value (h = 50 nm), the 2D and 3D models provide almost similar results in regard to the positions, shapes, and widths of the resonant modes in the transmission spectra [58,59]. In addition, the benefit of using the 1D approach resides in the analytical calculations' derivation, which enables us to understand the origin of each mode propagating in such structures.…”
Section: Basic Model and Theoretical Studymentioning
confidence: 96%
“…TPPs have been applied in sensors, [13,14] thermal emitters, [15,16] hot-electrons collection, [17] enhancement of light absorption, [18,19] and nanofocusing. [20] Due to the strong field confinement of TPPs, it would also be a suitable structure for investigating the effect of Rabi splitting as well as the performance of strong coupling. [21][22][23][24][25][26] Under strong coupling conditions, TPP and excitons will form a new quasi-particle-Tamm plasmon excitonpolariton.…”
Section: Introductionmentioning
confidence: 99%